2019
DOI: 10.1073/pnas.1817415116
|View full text |Cite
|
Sign up to set email alerts
|

p27 transcriptionally coregulates cJun to drive programs of tumor progression

Abstract: p27 shifts from CDK inhibitor to oncogene when phosphorylated by PI3K effector kinases. Here, we show that p27 is a cJun coregulator, whose assembly and chromatin association is governed by p27 phosphorylation. In breast and bladder cancer cells with high p27pT157pT198 or expressing a CDK-binding defective p27pT157pT198 phosphomimetic (p27CK−DD), cJun is activated and interacts with p27, and p27/cJun complexes localize to the nucleus. p27/cJun up-regulatesTGFB2to drive metastasis in vivo. Global analysis of p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 64 publications
3
56
0
Order By: Relevance
“…S2A; Supplementary Tables S4 and S5). Of note, we also identified other pathways with reported activities in the regulation of invasion, such as p27, FAS, and RAC, although their prevalence in the analysis and their documented association to this phenotype were minor (26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 74%
“…S2A; Supplementary Tables S4 and S5). Of note, we also identified other pathways with reported activities in the regulation of invasion, such as p27, FAS, and RAC, although their prevalence in the analysis and their documented association to this phenotype were minor (26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 74%
“…Low p27 expression has been correlated with an increased tumor stage and shorter overall survival by some investigators [27,28], whereas others see no predictive value of p27 [29,30], or even observe high p27 associated with poor prognosis [31]. Increased p27 has also been associated with loss of bladder cancer cell proliferation in several in vitro experiments [32], whereas others point to a role of p27 in activating epithelial-mesenchymal transformation [33] and forcing tumor cell migration and invasion [34]. p27 was only moderately diminished by SFN and the SFN-everolimus combination.…”
Section: Discussionmentioning
confidence: 99%
“…P27 is an unstructured multifunctional protein that affects a variety of biological processes from cell cycle regulation to cell migration and transcriptional regulation [36]. Notably, it has been reported that in addition to the loss of nuclear p27, the increase of cytoplasmic p27 in many human tumors is usually related to the invasiveness of tumors and the poor prognosis of patients [37,38]. Our results showed that the expression of p21 in Caski cells treated with TGF-β was significantly increased, which may be related to the inhibition of cell cycle arrest in G2/M phase.…”
Section: Discussionmentioning
confidence: 99%